Understanding the role of mitochondrial haemoglobin - an in silico approach - Katyal, Gunjan (2022)
About 60 years ago, Nobel Laureate, Max F. Perutz, who discovered the structure of the globular protein Haemoglobin (Hb), suggested that changes in the molecule were seen in neurodegenerative diseases and argued its role as a drug receptor. Neurodegeneration is more likely to be affected by a fundamental yet inevitable phenomenon of ageing. There has been sufficient evidence that changes in the powerhouse of the cell, mitochondria dysfunction, is one of the hallmarks of ageing and neurodegeneration. Yet we are still far off from deciphering direct links and pathways conclusively leading to it. The project was aimed to find that, if Hb is localised in the mitochondria, it must influence the proteins situated there. Hence to validate the theory the project entailed working on the unique and mysterious icefish that are the only vertebrate organisms without Hb and acted as a model to understand the differences observed in the presence/absence of this protein.